THE STUDY OF INDIRECT CALORIMETRY-BASED ENERGY EXCHANGE AMONG NEWBORN CHILDREN - M.V. Narogan; G.V. Yatsyk; E.V. Syutkina (Вопросы современной педиатрии, 2006)
The work deals with the research of indirect calorimetrya based energy exchange conducted on 145 newborn children of various gestational and postnatal age. The authors showed that thermal conditions are one of the most significant factors, which influence the size of energy exchange. there is dynamics of rest energy exchange (kcal/kg/day) and respiratory coefficient through the first months of life of the full aterm newborns with normal — or lowabirth weight, premature children of the 1st and 2nd degrees and very premature children.Key words: energy exchange, indirect calorimetry, respiratory coefficient, newborn children, premature children, very premature children.